Eksplorasi Muatan Kompetensi Tes Kemampuan Akademik Pada Jenjang Sekolah Dasar - Sulasmi, Sri; Kentin Sholikati; Sarjuna, Sarjuna; Mujoko, Mujoko; Siti Nur Fadhilah; Isfiyah Ratnawati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to explore the competency content in the Academic Ability Test (TKA) applied at the Elementary School level, specifically in Madrasah Ibtidaiyah Negeri 6 Boyolali and Madrasah Ibtidaiyah Negeri 5 Boyolali, and Madrasah Ibtidaiyah Negeri 1 Boyolali. This study focuses on identifying aspects of academic ability measured, the suitability of competency indicators with student characteristics, and the use of test results as a basis for learning planning. This research method uses a qualitative approach. The research subjects are teachers at Madrasah Ibtidaiyah Negeri 6 Boyolali and Madrasah Ibtidaiyah Negeri 5 Boyolali, and Madrasah Ibtidaiyah Negeri 1 Boyolali. The informants of this study are teachers. Data collection techniques are interviews, observation, and documentation. The results of this study are: 1) The Academic Ability Test (TKA) for Elementary Schools (SD) includes competency content in the subjects of Indonesian Language and Mathematics. For Indonesian Language, the focus is on reading skills of informational and fictional texts, including textual and inferential comprehension as well as evaluation. Meanwhile, the Mathematics TKA measures conceptual understanding, representation, reasoning, problem solving, and connections between concepts; 2) The role of the results of the TKA competency exploration in learning planning: a) Adjusting learning methods and materials; b) Using data as a reflection of improvement; c) Developing relevant learning resources; d) Helping determine remedial and enrichment; e) Supporting evidence-based formative assessment. The conclusion in this study is that the results of the TKA are used as a reference in designing more adaptive and effective learning strategies. This finding confirms that the exploration of the TKA competency content is an important step in improving the quality of the learning process at the MI level, especially in ensuring students' academic readiness according to their developmental stage.